7.3k views
2 votes
-5x + 3 = 8x + 9 – 3

1 Answer

3 votes


\text {Hi There! The answer to your problem is}


\fbox {x=-3/13}


\text {Your 1st Step will be to Simplify the Equation}


\text {-5x+3=8x+9+-3}


\text {-5x+3=(8x)+(9+-3) (Combine Like Terms)}


\text {-5x+3=8x+6}


\text {The Next Step is to Subtract 8x}


\text {-13x+3-3=6-3}


\text {-13x=3}


\text {The Final Step is to Divide by -13}


\text {-13x/13=3/-13}


\text {x=-3/13}


\text {Best of Luck!}


\text {-LimitedX}

User Chandima
by
4.7k points